The Effect of Asymmetric Oil Price Shocks on Industrial Production in Jordan - Asab, Noura Abu (International Journal of Economics and Financial Issues, 2017)
The aim of this paper is to examine the asymmetric effect of oil price shocks on economic activity in Jordan, proxied by industrial production growth. Accommodating for non-linearity and employing different oil price shock measures, the findings suggest that positive oil shocks have a negative and significant effect on growth, while oil price declines have no impact on growth. This suggests that drops in oil prices are not necessarily an incentive for industrial growth in oil-importing countries. Based on symmetry specifications, oil price shocks and growth are found to be negatively correlated. Keywords: Oil shock, Jordan, Oil importers, Nonlinearities JEL Classifications: O47, Q43, C50